Aspectos concorrenciais no mercado de leite fluido: um teste empírico no município de São Paulo - Politi, Ricardo Batista (2006)
The main purpose of this work is to characterize competition in the fluid milk market (long-shelf and pasteurized milk) in São Paulo considering evidences from retail price movements and market margins. It was applied the model proposed by Houck (1977) including the changes latter suggested by Carman and Sexton (2005). This approach separates the explanatory variables between price increases and price decreases paid to milk producers. This analysis allows to compare the different lags movements between prices increases and decreases and to study agents’ pricing strategies. Data ranges from December 1999 to December 2005, including milk retail price (source FIPE) and milk producer price (source CEPEA/USP). It is possible to conclude that competition in the long shelf market is different from the competition in the pasteurized milk market. Whereas in the long shelf market competition is closer to the perfect competitive market, the pasteurized market is far from competitive. To better understand these differences, it was considered the geographical relevant market and the retail area influence. The results allow some inferences for sector analysis and for public policies concerning the milk chain. The huge increase in the long shelf sales, when it has taken a major share in the fluid milk market, it has brought a higher competition in the processing and distribution milk industry, as long as a faster decrease price transmission to the consumer level. However, the mark-up pricing strategy on the retail level, as observed at the long shelf milk, reveals that at processor and at distribution level the industry has some market power. As a consequence price increases movements are higher transmitted at absolute level to the consumer marke.